Pengaruh Tegangan dan Waktu pada Proses Elektropolishing terhadap Surface Roghness Material Stainless Steel AISI 316L - Widodo, Teguh Dwi; Raharjo, Rudianto; Kusumaningsih, Haslinda; Bintarto, Redi; Siswoyo, Redi Cipto; Sasongko, Mega Nur (Jurnal Rekayasa Mesin, 2019)
The purpose of this work is to reveal the surface roughness and topography of AISI 316L stainless steel due to electropolishing processes. In this paper, AISI 316L was electropolished in various times of immersion and various voltage of the processes. The mechanism of electropolishing is eroding the surface of the substrate by controlling the electron excitation process. The electropolishing processes were carried out at 4, 5, and 6 minutes also in three different voltage 4, 6, and 8 volts. The results show that the surface roughness decrease as the treatment time and also as an increase in voltage.